Shaping of Cities’ Identities with Cultural Uniqueness: Handcraft Shops and Night Bazaar in Chiang Mai, Thailand, and Hanoi Old Quarter in Vietnam - Yekti Maunati (International Journal of Interreligious and Intercultural Studies, 2021)
A city usually has its own identity and cultural uniqueness with the markers of identity perhaps varying among museums, monuments, temples, theatre buildings, handcraft and traditional shops/markets and night bazaars and historical heritage sites, to mention a few. It is very common for cities in mainland Southeast Asia, like Bangkok, Chiang Mai, Phnom Penh, Luang Prabang and Hanoi to have handcraft markets/shops as well as night bazaars selling various handcrafts attributed to one ethnic group or another. Those handcraft shops/markets and night bazaars are often at least partly related to the promotion of tourism. However, they do not only exist for the sake of tourism, since the promotion of cultural uniqueness as the identity of a city is related to the feeling of pride and the very soul of the city. This paper will discuss the existing handcraft markets/shops and night bazaar in Chiang Mai (Thailand) as important elements of the city’ s icons and the Hanoi Old Quarter, a historical heritage area in Hanoi, where handcraft shops, night market, cafés and many more venues are integral to the identity of Hanoi. The fieldwork was conducted in Chiang Mai in 2004, 2005, 2009 and 2016 for a few days and in Hanoi in 2006, 2017, 2018 for a few days, especially using qualitative research. The discussion is divided into three parts: the First, giving a brief review of the identity of a city; the Second, touching on the issue of how the handcraft shops and the Night Bazaar in Chiang Mai are seen as the city icons; and Finally, the shaping of the Hanoi Old Quarter as Hanoi’s cultural icon/identity.